Abnormal Expression of Prostaglandins E2 and F2α Receptors and Transporters in Patients with Endometriosis. (9th July 2015) - Rakhila, Halima; Bourcier, Nathalie; Akoum, Ali; Pouliot, Marc
Abstract : Objective. To investigate the level of expression of prostaglandin receptivity and uptake factors in eutopic and ectopic endometrium of women with endometriosis. Design. Prospective study. Setting. Human reproduction research laboratory. Patients. Seventy-eight patients with endometriosis and thirty healthy control subjects. Intervention(s). Endometrial and endometriotic tissue samples were obtained during laparoscopic surgery. Main Outcome Measure(s). Real-time polymerase chain reaction assay of mRNA encoding prostaglandin E2 receptors (EP1, EP2, EP3, and EP4), prostaglandin F2 α receptor (FP), prostaglandin transporter (PGT), and multidrug resistance-associated protein 4 (MRP4); immunohistochemical localization of expressed proteins. Results. Marked increases in receptors EP3, EP4, and FP and transporters PGT and MRP4 in ectopic endometrial tissue were noted, without noticeable change associated with disease stage. An increase in EP3 expression and decreases in FP and PGT were observed in the eutopic endometrium of endometriosis patients in conjunction with the phases of the menstrual cycle. Conclusion(s). This study is the first to demonstrate a possible relationship between endometriosis and enhanced prostaglandin activity. In view of the wide range of prostaglandin functions, increasing cell receptivity and facilitating uptake in endometrial tissue could contribute to the initial steps of overgrowth and have an important role to play in the pathogenesis and symptoms of this disease.